Does Low Vitamin D Have a Role in Pediatric Morbidity and Mortality? An Observational Study of Vitamin D in a Cohort of 52 Postmortem Examinations. (November 2014) - Scheimberg, Irene; Perry, Leslie
Vitamin D is required for calcium absorption and normal bone mineralization; it has a key role in immune regulation against infections and is believed to be involved in immunomodulation in asthma. We did a retrospective analysis of 52 postmortem cases (aged 2 days to 10 years). Seventeen children had vitamin D deficiency (<25 nmol/L); 24 children had vitamin D insufficiency (25–49 nmol/L); 10 children had suboptimal vitamin D levels (50–79 nmol/L); and only 1 child had adequate levels (≥80 nmol/L). Three infants had fractures. Growth plate histology was abnormal in 10 cases with vitamin D deficiency (59%), but radiology was abnormal in only 3 of those cases. Eight infants (33%) with vitamin D insufficiency had abnormal histology, but radiology was normal in all cases. In 3 children hypocalcemia due to vitamin D deficiency was considered accountable for death; they all showed radiological and histological rickets: 2 babies had cardiomyopathy and a 3-year-old had hypocalcemic seizures. Children from all ethnic groups had a high proportion of low vitamin D levels. Vitamin D deficiency (the most common form of pediatric metabolic bone disease) is preventable and treatable. Profound hypocalcemia due to severe vitamin D deficiency can cause unexpected death in babies and young children. Measuring serum vitamin D levels postmortem may provide invaluable information on sudden unexplained death in 'at-risk' children. Vitamin D deficiency may be relevant in childhood asthma and in children with multiple infections and babies with bone fractures. Postmortem vitamin D levels are stable and easy to measure.